Utilização do choque osmótico na avaliação da viabilidade de sêmen criopreservado de ovinos - de Menezes, Gabriel Felipe Oliveira; Bittencourt, Rodrigo Freitas; Ribeiro Filho, Antônio de Lisboa; Chalhoub, Marcus; Bittencourt, Marta Freitas; Oba, Eunice [UNESP]; Bicudo, Sony Dimas [UNESP] (My University, 2014)
Tis study evaluated the use of hipoosmotic swelling test (HOST) with deionized water (0 mOsmol), as a method of post thaw ram semen evaluation and correlate their findings with different techniques of semen evaluation. Therefore, twenty semen samples of 20 different adult rams were assessed as for kinetic sperm parameters through computerized system (IVOS 12, Hamiton Torn Biosciences, Beverly, MA, EUA) and subjective analysis. Te sperm membranes viability was carried out by the association of fuorescent probes (propidium iodide, JC-1 and FITC-PSA). Te structural integrity of the plasma membrane was also studied through supravital test with eosin and the functional integrity of membrane evaluated by doing the hipoosmotic swelling test with deionized water (0 mOsmol), in the following proportions: One part of semen for 10 (HOST 10), 50 (HOST 50) and 100 (HOST 100) parts of water. After semen dilution in the different proportions it was fixed in formalin-bufered saline and analyzed with regard to percentage of HOST reactive sperm (bent/coiled). Te percentage of reaction obtained for HOST 10 (33,1%); HOST 50 (32,8%) and HOST 100 (31,8%) did not differ significantly. HOST 10 presented positive correlation with the plasma membrane integrity by the EOS (r = 0,80; p < 0,05). Positive correlations between HOST 50 and HOST 100 with sperm subpopulation with membrane integrity by fluorescence were observed (r = 0,83 and r = 0,85; p < 0,01). Te findings suggest that the HOST with deionized water can provide additional information for post thawing ram sperm viability evaluation.
Utilization of the osmotic shock to assess the frozen ram semen viability
Keywords: Deionized water; Frozen semen; Hipoosmotic swelling test; Ovine